Steel surface treatment method using high-entropy multi-component alloy co-permeation agent
Through the steel surface treatment technology of high-entropy multivariate alloy co-penetration agent, a dense multivariate alloy protective layer is formed, which solves the problems of insufficient corrosion resistance and wear resistance of steel equipment and components in the prior art, and significantly improves the neutral salt spray resistance and low cycle fatigue life.
Patent Information
- Application Number
- CN202411651097.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-07
AI Technical Summary
Existing steel surface treatment technology is difficult to effectively improve the corrosion and wear resistance of steel equipment and components economically, while maintaining the toughness and strength of the material.
Using high-entropy multi-alloy co-penetration agent, the zinc powder, zinc chloride, zinc aluminum-magnesium-copper alloy powder, AlCoCrFeNi2.1 five-membered high-entropy alloy powder are mixed and processed under vacuum high temperature conditions to form a dense multi-alloy protective layer. Through the mechanical energy-assisted seepage and cooling separation steps, the corrosion resistance and wear resistance of the seepage layer are improved.
It significantly improves the neutral salt spray resistance of steel components, extending from 400h to more than 5000h, and enhances the low-cycle fatigue life and tensile resistance of the workpiece, improving service life and safety.
Smart Images

Figure CN119571245A_ABST
Abstract
Description
Technical Field
[0001] The invention provides a steel surface treatment method using a high-entropy multi-element alloy co-penetrating agent, belonging to the technical field of metal surface treatment and metal anticorrosion. Background Art
[0002] Material surface protection technology is a technology that uses physical or chemical means to give and improve special properties on the surface of materials without changing the composition of the base material or weakening the strength of the base material (or weakening the strength of the base material without affecting its use), so as to meet the requirements of the material in engineering. Therefore, material surface protection technology is an effective way to improve the performance and life of materials.
[0003] The requirements for corrosion resistance and wear resistance of steel equipment and components are becoming increasingly stringent. In some cases, if precious metal materials are selected, the surface performance requirements can be met, but from an economic perspective, they are not always suitable. For most materials, toughness and hardness cannot be achieved at the same time. Generally speaking, alloy steel has high strength and toughness, but low hardness. Harsh scouring, abrasion, and corrosion environments are only for the surface of the material, and the requirements for the core are not high. If ordinary steel is selected with surface treatment, the same good effect can be achieved. Since the surface treatment layer is very thin, even if precious metals are used on the surface part, the cost is not high. Therefore, the preparation of coatings on the surface of steel not only plays the toughness of steel. It also plays the high corrosion resistance, high wear resistance, and high hardness of the alloy layer, which is often not achieved by using a single steel. Therefore, research and development of steel surface protection technology is of great significance for improving the service life and reliability of equipment and components; for improving the performance, quality and competitiveness of equipment; for the development of new technologies and for saving materials and energy.
[0004] Multi-component alloy co-penetration is one of the important methods for surface corrosion protection of steel parts. It uses the principle of atomic penetration and diffusion to form a multi-component alloy protective layer with a firm bond and uniform thickness on the surface of the steel parts after the multi-component alloy powder contacts the steel parts at a certain temperature. Compared with hot-dip galvanizing and electroplating processes, the multi-component alloy co-penetration process has many unique advantages, which are specifically reflected in the following aspects: such as simple process, low zinc consumption, energy saving, and no harm to the environment. Compared with other processes, the high-entropy multi-component alloy co-penetration process designed by the present invention emphasizes the reduction of the oxide layer of the penetration layer and the complementarity and coordination of multiple elements, so that the corrosion resistance of the penetration layer is further improved, and the neutral salt spray resistance is extended from 400h to 500h to more than 5000h. Summary of the invention
[0005] In order to solve the above problems, the technical scheme proposed in the present invention is: a steel surface treatment method using a high-entropy multi-element alloy co-infiltration agent, including the preparation of the high-entropy multi-element alloy co-infiltration agent and the steel surface treatment method; the preparation of the high-entropy multi-element alloy co-infiltration agent includes the following steps: S1, based on the total mass of the alloy, prepare 100 parts of zinc powder, 5-7 parts of zinc chloride, 5-9 parts of zinc-aluminum-magnesium-copper alloy powder, 8-12 parts of AlCoCrFeNi2.1 five-element high-entropy alloy powder, 0.6-1 part of lanthanum nitrate powder, and 1-2 parts of catalyst; S2, mix the raw materials prepared in S1 under vacuum and high temperature conditions, and add active catalysts and fillers; the steel surface treatment method includes the following steps: SS1, degreasing; SS2, rust removal; SS3, mechanical energy-assisted infiltration; SS4, cooling and separation.
[0006] As an improvement, in step S1, the average particle sizes of zinc powder, zinc-aluminum-magnesium-copper alloy powder, zinc chloride, AlCoCrFeNi2.1 five-element high entropy alloy powder, and lanthanum nitrate powder are all less than 75 μm; the zinc powder is obtained by distillation, has a particle size of 800 mesh and a zinc content of more than 98%.
[0007] As an improvement, in step S1, the preparation method of zinc-aluminum-magnesium-copper alloy powder is as follows: Zn.Al.Mg.Cu is prepared according to the mass percentage of Zn77%, Al21%, Mg0.3%, and Cu1.7%, the four materials are transferred into a vacuum arc melting furnace for melting, the vacuum is drawn to 0.01 atmosphere (atm), and then pure argon is filled to 0.2 atmosphere (atm), the melting temperature is 660-730°C, the temperature is kept for 0.5-1h, and the mixture is fully stirred, the Zn.Al.Mg.Cu alloy molten liquid is cooled by closed-loop anaerobic centrifugal atomization, the alloy block is turned over, the above melting action is repeated for more than five times, and finally the ingot is cooled and solidified on a water-cooled mold to form an ingot; after the ingot is crushed into particles, it is ground into fine powder by a machine, and the powder material with a particle size of less than 75μm can be obtained by sieving the obtained powder through a sieve.
[0008] As an improvement, in step S1, the preparation method of AlCoCrFeNi2.1 five-element high entropy alloy powder is as follows: prepare 8.6% Al, 18.3% CO, 16.2% Cr, 17% Fe, and the remaining component is Ni; when making, place them in a vacuum arc melting furnace from top to bottom according to the melting points of the main elements, evacuate the vacuum to 0.01 atmosphere (atm), and then fill with pure argon to 0.2 atmosphere (atm), after smelting evenly, wait for it to cool into an alloy block, turn the alloy block over, repeat the above smelting action for more than five times, and finally cool and solidify it into an ingot on a water-cooled mold; after the above ingot is crushed into particles, it is ground into fine powder by a machine, and the obtained powder is sieved through a sieve to obtain a powder material with a particle size of less than 75μm.
[0009] As an improvement, in step S2, the active catalyst added is CH 4 N 2 O, the added fillers are fly ash and floating beads; and the mixing treatment temperature is 380-440°C.
[0010] As an improvement, in step SS1, degreasing liquid is used for degreasing. The preparation method of the degreasing liquid is as follows: 30-40 g / L sodium hydroxide, 30-40 g / L sodium carbonate, 30-40 g / L trisodium phosphate, and 5 g / L sodium silicate (water glass) are mixed; the surface of the product is completely soaked with the degreasing liquid at 90-100°C, and stirring is performed.
[0011] As an improvement, in step SS2, a shot blasting machine is used to perform shot blasting and rust removal.
[0012] As an improvement, in step SS3, the method of mechanical energy-assisted infiltration is: a homemade 150KW resistance heating furnace; an adjustable motor is used as the power for the rotation of the infiltration box; the zinc infiltration box is 3.5m long, 0.8m wide, and 0.8m high, and is fully sealed. The entire infiltration process is completed in the infiltration box; the temperature of metal workpieces and multi-element powder alloys and products without special requirements is controlled at 380-440℃. Special products can reduce the temperature by about 350℃ for insulation according to process requirements (selected according to product materials); two sets of temperature measuring devices can measure the heating The temperature in the furnace can also be measured to determine the temperature in the infiltration box, so that the temperature can be controlled within the optimal range. An adjustable speed device is used, and the speed of the infiltration box changes from fast to slow during the production process. Before heating, the product is first loaded into the infiltration box, and then fillers and various alloy powders are added. The closed container is loaded into the heating furnace and begins to rotate (2-3r / min) while heating. When the temperature of the infiltration box reaches 200°C in about an hour, the speed is reduced to 1-1.5r / min. When the temperature in the infiltration box rises to 380-420°C, it is kept warm for 4-6h.
[0013] As an improvement, in step SS4, after the infiltration is completed, the infiltration box is placed on the separation equipment, the temperature is reduced to within 200°C, the infiltration box cover is opened, the product and the filler are cooled and separated at a speed of 1-2r / min, and the workpiece is removed and the surface dust is cleared.
[0014] Beneficial effects of the present invention:
[0015] 1. The present invention adopts a multi-element alloy co-penetration agent to form a smooth, dense, corrosion-resistant penetration layer on steel components. After 5000 hours of salt spray test, the surface structure of the steel components is intact, which can ensure that steel components such as railways, power telecommunications, cross-sea bridges, and marine facilities have high-strength anti-corrosion performance and improve the safety of metal components.
[0016] 2. The present invention utilizes mechanical vibration impact loads to act on the surface of metal materials to achieve the purpose of forming a nano-sized surface layer on the surface of the workpiece. A combination of thermal control method, kinetic method and chemical method is adopted in the process of high entropy multi-element alloy co-penetration treatment. During the production process, a large number of crystallization cores are formed in the alloy, and the crystal growth is prevented, the nucleation mechanism of the alloy is strengthened, and while the alloy grains are refined, the size of the primary carbides and the strengthening phase γ' in the high-temperature alloy is reduced, and the morphology is improved. High entropy multi-element alloy co-penetration treatment greatly improves the low-cycle fatigue life of the workpiece under medium and low temperature conditions (≤700°C), and significantly reduces the dispersion of the workpiece mechanical property data, thereby improving the design tolerance of the workpiece. At the same time, this technology also improves the tensile strength and durability of the workpiece to a certain extent. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The present invention is a flow chart of the steel surface treatment method.
[0018] Figure 2 A diagram is made for the zinc-aluminum-magnesium-copper alloy powder of the present invention.
[0019] Figure 3 This is a diagram of the preparation of the AlCoCrFeNi2.1 quinary high entropy alloy powder of the present invention.
[0020] Figure 4 Schematic diagram of the active catalyst of the present invention.
[0021] Figure 5 This is a test result diagram of Example 1 of the present invention.
[0022] Figure 6 This is a test result diagram of Example 2 of the present invention.
[0023] Figure 7 This is a test result diagram of Example 3 of the present invention.
[0024] Figure 8 This is a test result diagram of Example 4 of the present invention.
[0025] Fig. 9 This is a test result diagram of Example 5 of the present invention. DETAILED DESCRIPTION
[0026] The present invention is further described below in conjunction with the accompanying drawings.
[0027] according to Figure 1As shown: The present invention provides a steel surface treatment method using a high-entropy multi-element alloy co-infiltration agent: including the preparation of the high-entropy multi-element alloy co-infiltration agent and the steel surface treatment method; the preparation of the high-entropy multi-element alloy co-infiltration agent includes the following steps: S1, based on the total mass of the alloy, prepare 100 parts of zinc powder, 5-7 parts of zinc chloride, 5-9 parts of zinc-aluminum-magnesium-copper alloy powder, 8-12 parts of AlCoCrFeNi2.1 five-element high-entropy alloy powder, 0.6-1 part of lanthanum nitrate powder, and 1-2 parts of catalyst; S2, mix the raw materials prepared in S1 under vacuum and high temperature conditions, and add active catalysts and fillers; the steel surface treatment method includes the following steps: SS1, degreasing; SS2, rust removal; SS3, mechanical energy-assisted infiltration; SS4, cooling and separation.
[0028] In step S1, the average particle sizes of zinc powder, zinc-aluminum-magnesium-copper alloy powder, zinc chloride, AlCoCrFeNi2.1 five-element high entropy alloy powder, and lanthanum nitrate powder are all less than 75 μm; the zinc powder is obtained by distillation, and the zinc powder has a particle size of 800 mesh and a zinc content of more than 98%.
[0029] In step S1, the preparation method of zinc-aluminum-magnesium-copper alloy powder is: Zn.Al.Mg.Cu is mixed according to the mass percentage of Zn77%, Al21%, Mg0.3%, and Cu1.7%. The alloy contains a small amount of magnesium, which can prevent intergranular corrosion and delay the eutectoid reaction process; copper causes solid solution strengthening of the alloy and hinders the eutectoid transformation. The four materials are transferred into a vacuum arc melting furnace for melting, and the vacuum is drawn to 0.01 atmosphere (atm), and then pure argon is filled to 0.2 atmosphere (atm). To ensure that the alloy will not be oxidized in large quantities, the melting temperature is 660-730°C, and the temperature is kept for 0.5-1h. After being fully stirred, the Zn.Al.Mg.Cu alloy molten liquid is cooled by closed-loop anaerobic centrifugal atomization, and the alloy block is turned over, and the above melting action is repeated for more than five times to ensure that all the main elements are evenly mixed. Finally, the ingot is cooled and solidified on a water-cooled mold; after the above ingot is crushed into particles, it is ground into fine powder by a machine, and the obtained powder is sieved through a sieve to obtain a powder material with a particle size of less than 75μm, such as Figure 2 shown.
[0030] In step S1, the preparation method of AlCoCrFeNi2.1 five-element high entropy alloy powder is as follows: prepare 8.6% of Al, 18.3% of CO, 16.2% of Cr, 17% of Fe, and the remaining component is Ni; when making, according to the melting point of each main element, place it in a vacuum arc melting furnace from top to bottom, draw a vacuum to 0.01 atmosphere (atm), and then fill it with pure argon to 0.2 atmosphere (atm). To ensure that the alloy will not be oxidized in large quantities, after smelting evenly, wait for it to cool into an alloy block, turn the alloy block over, and repeat the above smelting action for more than five times to ensure that all the main elements are evenly mixed, and finally cool and solidify it on a water-cooled mold to form an ingot; after the above ingot is crushed into particles, it is ground into fine powder by a machine, and the obtained powder is sieved through a sieve to obtain a powder material with a particle size of less than 75μm, such as Figure 3 shown.
[0031] like Figure 4 As shown, in step S2, the active catalyst added is CH 4 N 2 O, the traditional process generally uses ammonium chloride as an activator, but ammonium chloride is decomposed by heat in a high temperature environment to produce HCL gas. Excessive HCL gas will cause corrosion on the workpiece surface, and black spots will often appear on the workpiece surface, including continuous corrosion of the infiltration furnace wall, which will reduce the quality of the infiltration layer and consume too much zinc, aluminum, magnesium, nickel and other materials. This application uses CH 4 N 2 O (urea) as an activator, firstly, the penetration thickness is significantly thicker than that of ammonium chloride as an activator, and secondly, there is no chlorine corrosion, and the product quality is easier to guarantee. The added fillers are fly ash and floating beads; as a filling material, the hollow structure of the floating beads makes it light. After mixing with alloy powder, fly ash and other ingredients in the penetrant formula, the penetrant can better wrap the steel products during the heating process, ensuring the uniformity of the multi-element alloy co-penetration process. Improve fluidity: The addition of floating beads can improve the fluidity of the penetrant, making it easier for the penetrant to fully contact with the inner and outer holes, concave and convex surfaces, inner and outer threads of steel products, accelerate the penetration speed, and ensure the uniform penetration layer on the inner and outer surfaces of steel products. At the same time, when fly ash and floating beads account for a large proportion in the formula, it is beneficial for the alloy powder and steel products to be buried in the penetrant in the high-temperature container, reducing contact with the air, thereby avoiding excessive oxidation of the alloy powder at high temperature, greatly enhancing the corrosion resistance of the surface alloy, and at the same time improving the number of uses and quality of the penetrant. The mixing treatment temperature is 380-440℃.
[0032] The workpiece must be degreased before high entropy multi-element alloy co-infiltration. Otherwise, due to the increase in temperature, the residue after the oil film is sintered on the surface of the product will be sintered together with the filler, so that the steel surface is filled with sintered materials, which are difficult to remove during rework. On the other hand, the oil film sintered materials mixed into the charge will not be separated from the charge, resulting in the scrapping of the charge and unnecessary losses. In step SS1, degreasing is performed using a degreasing liquid. The preparation method of the degreasing liquid is as follows: 30-40g / L sodium hydroxide, 30-40g / L sodium carbonate, 30-40g / L trisodium phosphate, and 5g / L sodium silicate (water glass) are mixed; the surface of the product is completely wetted with the degreasing liquid at 90-100°C, and stirred. When the degreasing speed slows down and the quality decreases, raw materials should be added to the solution, and the degreasing liquid must be replaced after a certain period of time.
[0033] In step SS2, a shot blasting machine is used to perform shot blasting and rust removal.
[0034] In step SS3, the method of mechanical energy-assisted infiltration is as follows: a self-made 150KW resistance heating furnace; an adjustable motor is used as the power for the rotation of the infiltration box; the zinc infiltration box is 3.5m long, 0.8m wide, and 0.8m high, and is fully sealed. The entire infiltration process is completed in the infiltration box; the temperature of the metal workpiece and the multi-element powder alloy and the product without special requirements is controlled at 380-440℃. Special products can reduce the temperature by about 350℃ for insulation according to the process requirements (selected according to the product material); two sets of temperature measuring devices can measure the temperature in the heating furnace The temperature can be measured and the temperature in the infiltration box can be controlled within the optimal range. The adjustable speed device is used, and the speed of the infiltration box changes from fast to slow during the production process. Before heating, the product is first loaded into the infiltration box, and then the filler and various alloy powders are added. The closed container is loaded into the heating furnace and starts to rotate (2-3r / min) while heating. When the temperature of the infiltration box reaches 200℃ in about 1 hour, the speed is reduced to 1-1.5r / min. When the temperature in the infiltration box rises to 380-420℃, it is kept warm for 4-6h.
[0035] In step SS4, after the infiltration is completed, the infiltration box is placed on the separation equipment, the temperature is reduced to within 200°C, the infiltration box cover is opened, the product and the filler are cooled and separated at a speed of 1-2r / min, and the workpiece is removed and the surface dust is cleared.
[0036] Example 1
[0037] Based on the total mass of the alloy, a high-entropy multi-element alloy co-infiltration agent was prepared with 100 parts of zinc powder, 5 parts of zinc chloride, 5 parts of zinc-aluminum-magnesium-copper alloy powder, 8 parts of AlCoCrFeNi2.1 five-element high-entropy alloy powder, 0.6 parts of lanthanum nitrate powder, and 1 part of catalyst. After the surface of the steel workpiece was treated with the high-entropy multi-element alloy co-infiltration agent, the neutral salt spray resistance and ultrasonic hardness of the steel workpiece were tested, and the following results were obtained: Figure 5 of the test results.
[0038] Example 2
[0039] Based on the total mass of the alloy, a high entropy multi-element alloy co-infiltration agent was prepared with 100 parts of zinc powder, 6 parts of zinc chloride, 6 parts of zinc-aluminum-magnesium-copper alloy powder, 9 parts of AlCoCrFeNi2.1 five-element high entropy alloy powder, 0.7 parts of lanthanum nitrate powder, and 1 part of catalyst. After the surface of the steel workpiece was treated with the high entropy multi-element alloy co-infiltration agent, the neutral salt spray resistance and ultrasonic hardness of the steel workpiece were tested, and the following results were obtained: Figure 6 of the test results.
[0040] Example 3
[0041] Based on the total mass of the alloy, a high-entropy multi-element alloy co-infiltration agent was prepared with 100 parts of zinc powder, 7 parts of zinc chloride, 7 parts of zinc-aluminum-magnesium-copper alloy powder, 10 parts of AlCoCrFeNi2.1 five-element high-entropy alloy powder, 0.8 parts of lanthanum nitrate powder, and 1 part of catalyst. After the surface of the steel workpiece was treated with the high-entropy multi-element alloy co-infiltration agent, the neutral salt spray resistance and ultrasonic hardness of the steel workpiece were tested, and the following results were obtained: Figure 7 of the test results.
[0042] Example 4
[0043] Based on the total mass of the alloy, a high-entropy multi-element alloy co-infiltration agent was prepared with 100 parts of zinc powder, 7 parts of zinc chloride, 8 parts of zinc-aluminum-magnesium-copper alloy powder, 11 parts of AlCoCrFeNi2.1 five-element high-entropy alloy powder, 0.9 parts of lanthanum nitrate powder, and 2 parts of catalyst. After the surface of the steel workpiece was treated with the high-entropy multi-element alloy co-infiltration agent, the neutral salt spray resistance and ultrasonic hardness of the steel workpiece were tested, and the following results were obtained: Figure 8 of the test results.
[0044] Example 5
[0045] Based on the total mass of the alloy, a high-entropy multi-element alloy co-infiltration agent was prepared with 100 parts of zinc powder, 7 parts of zinc chloride, 9 parts of zinc-aluminum-magnesium-copper alloy powder, 12 parts of AlCoCrFeNi2.1 five-element high-entropy alloy powder, 1 part of lanthanum nitrate powder, and 2 parts of catalyst. After the surface of the steel workpiece was treated with the high-entropy multi-element alloy co-infiltration agent, the neutral salt spray resistance and ultrasonic hardness of the steel workpiece were tested, and the following results were obtained: Fig. 9 of the test results.
[0046] Main performance comparison test results
[0047] Test items Example 1 Example 2 Example 3 Example 4 Example 5 Neutral salt spray resistance, H 3650 4550 4820 5340 5680 Ultrasonic hardness, HRC 41.9 43.5 45.4 51.9 57.7
[0048] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it, without departing from the purpose of the invention, they can design a structure and embodiment similar to the technical solution without creativity, which should belong to the protection scope of the present invention.
Claims
1. A method for treating steel surface using a high entropy multi-element alloy co-penetrating agent, characterized in that: Including the preparation of high entropy multi-element alloy co-infiltration agent and steel surface treatment method; The preparation of the high entropy multi-element alloy co-infiltration agent comprises the following steps: S1, based on the total mass of the alloy, preparing 100 parts of zinc powder, 5-7 parts of zinc chloride, 5-9 parts of zinc-aluminum-magnesium-copper alloy powder, 8-12 parts of AlCoCrFeNi2.1 five-element high entropy alloy powder, 0.6-1 part of lanthanum nitrate powder, and 1-2 parts of catalyst; S2, mixing the raw materials prepared in S1 under vacuum and high temperature conditions, and adding active catalysts and fillers; The steel surface treatment method comprises the following steps: SS1, degreasing; SS2, rust removal; SS3, mechanical energy-assisted infiltration; SS4, cooling and separation.
2. A method for treating steel surface using a high entropy multi-element alloy co-penetrating agent according to claim 1, characterized in that: In step S1, the average particle sizes of zinc powder, zinc-aluminum-magnesium-copper alloy powder, zinc chloride, AlCoCrFeNi2.1 five-element high entropy alloy powder, and lanthanum nitrate powder are all less than 75 μm; the zinc powder is obtained by distillation, and the zinc powder has a particle size of 800 mesh and a zinc content of more than 98%.
3. A method for treating steel surface using a high entropy multi-element alloy co-penetrating agent according to claim 1, characterized in that: In step S1, the preparation method of zinc-aluminum-magnesium-copper alloy powder is as follows: Zn.Al.Mg.Cu is prepared according to the mass percentage of Zn77%, Al21%, Mg0.3%, and Cu1.7%, the four materials are transferred into a vacuum arc melting furnace for melting, the vacuum is drawn to 0.01 atmosphere (atm), and then pure argon is filled to 0.2 atmosphere (atm), the melting temperature is 660-730°C, the temperature is kept for 0.5-1h, and the mixture is fully stirred, the Zn.Al.Mg.Cu alloy molten liquid is cooled by closed-loop anaerobic centrifugal atomization, the alloy block is turned over, the above melting action is repeated for more than five times, and finally the ingot is cooled and solidified on a water-cooled mold to form an ingot; after the ingot is crushed into particles, it is ground into fine powder by a machine, and the powder material with a particle size of less than 75μm can be obtained by sieving the obtained powder through a sieve.
4. A method for treating steel surface using a high entropy multi-element alloy co-penetrating agent according to claim 1, characterized in that: In step S1, the preparation method of AlCoCrFeNi2.1 five-element high entropy alloy powder is as follows: prepare 8.6% of Al, 18.3% of CO, 16.2% of Cr, 17% of Fe, and the remaining component is Ni; when making, place them in a vacuum arc melting furnace from top to bottom according to the melting points of the main elements, evacuate the vacuum to 0.01 atmosphere (atm), and then fill with pure argon to 0.2 atmosphere (atm), after smelting evenly, wait for it to cool into an alloy block, turn the alloy block over, repeat the above smelting action for more than five times, and finally cool and solidify it into an ingot on a water-cooled mold; after the above ingot is crushed into particles, it is ground into fine powder by a machine, and the obtained powder is sieved through a sieve to obtain a powder material with a particle size less than 75μm.
5. The method for treating steel surface using a high entropy multi-element alloying agent according to claim 1, characterized in that: In step S2, the added active catalyst is CH4N2O, and the added filler is fly ash and floating beads; and the mixing treatment temperature is 380-440°C.
6. A method for treating steel surface using a high entropy multi-element alloy co-penetrating agent according to claim 1, characterized in that: In step SS1, degreasing is performed using a degreasing liquid, and the degreasing liquid is prepared by mixing 30-40 g / L sodium hydroxide, 30-40 g / L sodium carbonate, 30-40 g / L trisodium phosphate, and 5 g / L sodium silicate (water glass); the product surface is completely soaked with the degreasing liquid at 90-100°C, and stirred.
7. A method for treating steel surface using a high entropy multi-element alloying agent according to claim 1, characterized in that: In step SS2, a shot blasting machine is used to perform shot blasting and rust removal.
8. The method for treating steel surface using a high entropy multi-element alloying agent according to claim 1, characterized in that: In step SS3, the method of mechanical energy-assisted infiltration is as follows: a self-made 150KW resistance heating furnace; an adjustable motor is used as the power for the rotation of the infiltration box; the zinc infiltration box is 3.5m long, 0.8m wide, and 0.8m high, and is fully sealed. The entire infiltration process is completed in the infiltration box; the temperature of the metal workpiece and the multi-element powder alloy and the product without special requirements is controlled at 380-440℃. Special products can reduce the temperature by about 350℃ for insulation according to the process requirements (selected according to the product material); two sets of temperature measuring devices can measure the temperature in the heating furnace The temperature can be measured and the temperature in the infiltration box can be controlled within the optimal range. The adjustable speed device is used, and the speed of the infiltration box changes from fast to slow during the production process. Before heating, the product is first loaded into the infiltration box, and then the filler and various alloy powders are added. The closed container is loaded into the heating furnace and starts to rotate (2-3r / min) while heating. When the temperature of the infiltration box reaches 200℃ in about 1 hour, the speed is reduced to 1-1.5r / min. When the temperature in the infiltration box rises to 380-420℃, it is kept warm for 4-6h.
9. A method for treating steel surface using a high entropy multi-element alloying agent according to claim 8, characterized in that: In step SS4, after the infiltration is completed, the infiltration box is placed on the separation equipment, the temperature is reduced to within 200°C, the infiltration box cover is opened, the product and the filler are cooled and separated at a speed of 1-2r / min, and the workpiece is removed and the surface dust is cleared.